Perancangan Perbaikan Sistem Sampling Penerimaan Mutu pada Proses Produksi Divisi Painting & Sticker PT. X - Reynold Bernadi (Jurnal Titra, 2020)
This project aims to provide a design of an improvised acceptance sampling system as a part of the Quality Control (QC) activity in some production processes of Painting & Sticker Division at PT. X. Repair calls for defectives known externally until receiving more customer complaints become some continuous concerns for the company. One technique for analyzing its sampling system is through looking to its Probability of Acceptance (Pa), Average Outgoing Quality (AOQ), and Average Total Inspection (ATI) value. This project sets AOQ value as the topmost judgement parameter to determine a better acceptance sampling system. This is due to external failures and continuous complaints acquired in which caused by a poor quality detached from the Painting & Sticker Division. Result shows that the current acceptance sampling system produces a thin gap between its AOQ and initial quality value (calculated from the average defect/unit in June-December 2019). On the other hand, its AOQ given by the improvised acceptance sampling system shows a lower value in comparison. A lower AOQ of an acceptance sampling system will benefit company at some aspects, such as decrease of external failure cost and complaints.